Research progress on the application of nanoparticle drug delivery systems in local drug treatment of periodontitis - ZHANG Xinjian (Editorial Department of Journal of Prevention and Treatment for Stomatological Diseases, 2022)
Periodontitis is a common oral disease that represents one of the main causes of tooth loss in adults. In recent years, the application of nanotechnology has provided a new drug delivery system and innovative therapy for the treatment of periodontitis and opens up new prospects for the regeneration of periodontal tissue. The nanoparticle drug delivery system is composed of degradable carrier materials and drugs. Compared with the traditional film, namely, the fragment and strip-shaped periodontal local drug delivery system, the nanoparticle drug delivery system has the characteristics of biopharmaceuticals and pharmacokinetics. Moreover, it has special advantages, including controlled release of drugs, long-term maintenance of drug concentration, biodegradability and biocompatibility, etc. Antibiotics, protein drugs, such as growth factors, and nucleic acids used for gene delivery or mRNA knockout can be absorbed or dissolved in nanoparticles. Liposomes and polymer nanoparticle delivery systems can target bacteria and specific host cells. Inorganic nanoparticles and nanocrystals have good antibacterial activity that can promote periodontal tissue regeneration and play an important role in bone regeneration and bone repair. Dendrimers have internal hydrophobic and external hydrophilic structures and are good drug carriers for periodontitis.